Extracellular matrix metalloproteinase inducer in brain ischemia and intracerebral hemorrhage - Liu, Yang; Mu, Yanling; Li, Zhe; Yong, Voon Wee; Xue, Mengzhou (Frontiers in Immunology, 2022)
Increasing evidences from preclinical and clinical studies link neuroinflammation to secondary brain injury after stroke, which includes brain ischemia and intracerebral hemorrhage (ICH). Extracellular matrix metalloproteinase inducer (EMMPRIN), a cell surface transmembrane protein, is a key factor in neuroinflammation. It is widely elevated in several cell types after stroke. The increased EMMPRIN appears to regulate the expression of matrix metalloproteinases (MMPs) and exacerbate the pathology of stroke-induced blood-brain barrier dysfunction, microvascular thrombosis and neuroinflammation. In light of the neurological effects of EMMPRIN, we present in this review the complex network of roles that EMMPRIN has in brain ischemia and ICH. We first introduce the structural features and biological roles of EMMPRIN, followed by a description of the increased expression of EMMPRIN in brain ischemia and ICH. Next, we discuss the pathophysiological roles of EMMPRIN in brain ischemia and ICH. In addition, we summarize several important treatments for stroke that target the EMMPRIN signaling pathway. Finally, we suggest that EMMPRIN may have prospects as a biomarker of stroke injury. Overall, this review summarizes experimental and clinical evidences of the role of EMMPRIN in stroke and provides insights into its pathological mechanisms.